Spatial Attention Does Not Modulate Holistic Face Processing, Even When Multiple Faces are Present. (December 2014) - Norman, Liam J; Tokarev, Alexander
The perception of faces is often considered to be unique in comparison with that of other objects in the world. The fact that faces are processed not by their constituent components but by the spatial configuration between those components (holistic face processing—HFP) is often used to support this. Despite two decades of research, however, there is no consensus as to whether or not HFP is a process that is subject to attentional modulation. Here, in two experiments, we used a method to direct spatial attention not previously used in studies of HFP—an exogenous spatial cue—as it offers a robust, rapid, and involuntary method of directing attention. In one experiment we demonstrate that the degree of HFP afforded to a face is not reduced when attention is directed away from that face. In a second experiment we replicate this finding even when the face is simultaneously flanked by other faces—a condition under which a face-specific processing module would, hypothetically, be more sensitive to attentional guidance. These results add to the argument that HFP is carried out independently of attention.